Triptycene end-capped quinoxalinophenanthrophenazines (QPPs): Influence of substituents and conditions on aggregation in the solid state - Ueberricke, Lucas; Holub, Daniel; Kranz, Julian; Rominger, Frank; Elstner, Marcus; Mastalerz, Michael (Chemistry - a European journal, 2019)
Triptycene end-capped quinoxalinophenanthrophenazine reveals a coplanar arrangement with a high overlap of the π planes. Four structurally related model compounds bearing electron-withdrawing or -donating groups were synthesized, and their optoelectronic properties were characterized by using cyclovoltammetry, absorption- and emission spectroscopy as well as theoretical calculations. The directional robustness of the triptycene end-capping of these compounds was tested by using single-crystal X-ray diffraction. The impact of solvents and crystallization conditions has also been investigated. In total, 17 single-crystal structures were obtained. Each structure was evaluated for its potential charge-transfer capability taking into account the overall molecular packing, solvent enclathration and the structural overlap of the π planes of adjacent molecules. For this purpose, charge-transfer integrals were also calculated for every π-stacked dimer.
Gesehen am 19.03.2020